RATER AGREEMENT AND DISAGREEMENT IN THE MEASUREMENT OF ENGLISH ARTICLE ACQUISITION SUPPLIANCE AND ACCURACY - Upor, Rose Acen (LLT Journal: A Journal on Language and Language Teaching, 2021)
This study combines language assessment processes and interlanguage analysis techniques to determine rater agreement and disagreement in assessing English article acquisition. Employing native English speaking and non-native English speaking raters, picture sequence narratives that were written by English as a Foreign Language (EFL) learners (n=97) were coded and scored for suppliance-in-obligatory context (SOC) and target-like utterance (TLU). Although the kappa statistic revealed a fair agreement between raters (0.17 – 0.33), content analysis methods revealed much higher agreement (88.29% - 94.07%). Furthermore, language background effects between the raters could not be substantiated however the results demonstrated a discernable disagreement pattern between them. Thus, the study recommends the inclusion of a foreign language teaching background as a factor for rater selection to minimize language background effects on rating language assessments.